Clarification and capture of high‐concentration refold pools for E. coli‐based therapeutics using expanded bed adsorption chromatography. (13th November 2013) - Xu, Xuankuo; Hirpara, Jeet; Epting, Kevin; Jin, Mi; Ghose, Sanchayita; Rieble, Siegfried; Li, Zheng Jian
<x xml:space="preserve">Abstract</x> Expanded bed adsorption (EBA) chromatography was investigated for clarification and capture of high‐concentration refold pools of Escherichia coli‐based therapeutics. Refolding of denatured inclusion bodies (IBs) at high protein concentration significantly improved product throughput; however, direct filtration of the refold materials became very challenging because of high content of protein precipitates formed during refolding. In addition, irreversible protein precipitation caused by high local concentration was encountered in packed bed capture during cation exchange chromatography elution, which limited column loading capacity and capture step productivity. In this study, the two issues are addressed in one unit operation by using EBA. Specifically, EBA can handle feed streams with significant amount of particles and precipitates, which eliminated the need for refold pool clarification through filtration. The relatively broad EBA elution profile is particularly suitable for proteins of low solubility and can effectively avoid product loss previously associated with on‐column precipitation during capture. As the EBA resin (RHOBUST® FastLine SP IEX) used here has unique properties, it can be operated at high linear velocity (800–1, 600 cm/h), while achieving a selectivity and impurity clearance largely comparable to the packed bed resin of the same ligand chemistry (SP Sepharose FF). Furthermore, the filtration of the EBA elution pool is easily manageable within facility capability. Overall, this study demonstrates that the EBA process helps debottleneck the purification of high‐turbidity refold pools by removing precipitates and concurrently capturing the product, which can be applied to other E. coli‐based therapeutics that also requires refolding of IBs. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:113–123, 2014